The role of knowledge management processes in Creative marketing - النعيمي, صلاح عبد القادر; عذيب, عامر فدعوس (Journal of Economics and Administrative Sciences, 2016)
The research aims to measure the impact of knowledge management processes individually and in total in the innovative marketing.We depart search of a problem expressed in a number of intellectual and practical questions, the application of this research in the General Company for Vegetable Oil Industry, represented composed a sample of (63) (Director General and Deputy Director General and Director of the Department and the Division) in the company researched, it has been designed measuring instrument to collect the necessary data either statistical means they are the percentage and the arithmetic mean and standard deviation and coefficient of variation and the coefficient of simple correlation and model of simple regression and style track analysis The main results there was correlation between the informational monitoring systems and knowledge management processes and marketing innovative, as well as there effect systems informational monitoring overall in innovative marketing and the impact of knowledge management processes in the overall innovative marketin And to highlight the novelty of its variables, for being a modern subjects that newly emerged in recent years, it did not receive the attention of researchers and specialists and then they are trying to stir up interest in the issue of the impact of knowledge management processes to achieve innovative marketing, which calls for the need for the pilot to go to discuss the relationship between them                            The researcher also sought to clarify the theoretical concepts of variables public search form and construction company concerned with the importance of knowledge management processes in particular, identifying the application in the company surveyed to reach scientific conclusions can be aimed at the level of the overall importance of these mechanisms.